A numerical study of the response of buried steel pipelines undergoing strike-slip fault. (August 2019) - Gawande, Kshitij; Kiran, Raj; Cherukuri, H.P.
Abstract: Sudden ground motions resulting from seismic events can cause severe damage to buried pipelines resulting in fuel supply disruption and significant economic losses. The objective of this numerical study is to model and analyze the response of a buried pipeline in a strike-slip fault movement. Here, the interaction of the pipeline with the surrounding soil due to sudden ground movement has been studied by taking into account the contact between the pipeline and the soil, the nonlinear response of soil, and the material and geometrical non-linearities. The pipeline is assumed to be made of APIX65 grade steel. The material behavior is assumed to be governed by J2, rate-independent plasticity theory with strain-hardening included. The onset of buckling-mode failure in the pipeline has been studied for different pipe diameter-to-thickness ratios, the internal pressure, the fault displacement and fault offset rates to better understand the pipeline response due to seismic loads. Study predicts a systematic pre-buckling pattern of a pipe undergoing fault. This study also shows that fault resistance increases with higher diameter to thickness ratio and lower internal pressure. Moreover, the fault resistance counter-intuitively increases with an increase in fault offset rate. Highlights: Study captures onset of buckling in a buried steel pipeline undergoing strike-slip fault. Effect of pipe diameter to thickness ratio on the shape and the onset of buckling has been studied. Study concludes that resistance to the fault movement increases as the fault offset rate increases. Different buckling shape has been observed when internal pressure is present in the pipe. An optimal internal pressure range is observed for better fault resistance in a buried pipe.